Underpricing of IPOs in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Finance at Massey University - Clegg, Michael Brian (Massey University, 1997)
This study provides further evidence of 'underpricing' of initial public offerings ("IPOs") in New Zealand. IPOs are frequently issued at prices substantially less than the market price on the first day of listing. Recent literature has widely documented such IPO 'underpricing' and adequately established that IPOs of common stock are underpriced. This study examines the underpricing of 148 New Zealand IPOs between 1982 and 1997. The average market adjusted underpricing was 16.44% (median 10.05%), measured from offering date to list date, a level consistent with underpricing experienced in other markets,1 but lower than previous studies of the New Zealand market. This study makes two contributions to the existing IPO literature. First it performs a thorough univariate analysis of commonly cited reasons for underpricing with respect to the New Zealand market, and secondly it develops a multiple regression model. The model provides increased understanding of underpricing but due to a low R2, is not recommended to be used by market participants to predict future underpricing. This study finds that New Zealand IPO underpricing for issues between 1982 and 1997 vary in a manner consistent with the model of Rock (1986), and the extension of this by Beatty and Ritter (1986). It also finds evidence of the relationship between IPO underpricing and underwriter reputation consistent with Carter and Manaster (1990) and the relationship between IPO underpricing and issue market conditions consistent with Ritter (1984) and Ibbotson, Sindelar and Ritter (1988). The model accounts for underwriter reputation, the market conditions that prevail during the issue, ex ante uncertainty of the issuing firm, and a signalling effect consistent with Rock's (1986) "winners' curse."
Keywords: New Zealand Corporations; Valuation; Stock Prices; Securities Listing; Going public (Securities)